Study on the stress characteristic and fatigue life of the shredder pin. (January 2016) - Zhou, Xianyan; Hu, Zhili; Qin, Xunpeng; Tao, Yijun; Hua, Lin
Abstract: The hammer shredder is the key equipment for cyclic utilization of retired car bodies. The axes' pin is the main component of the shredder, but it is damaged easily. To improve the shredding efficiency and lengthen the changing life of the shredder pin, it is significant to study its stress characteristic and the fatigue life. In this article, the complex force conditions of the shredder pin at the normal working condition were studied briefly by mechanics analysis method. The stress characteristics and fatigue life of the pin were analyzed by the finite element transient analysis method. The maximum stress distribution law of the shredder pin was found and the fracture mechanism of the retired car bodies was revealed. Furthermore, the reliability of the simulation results was verified by the experiment. It was found that when the pin rotates around the main shaft counterclockwise, the maximum stress of the pin at 0° of the main shaft is higher than other positions. Additionally, along the axial direction, the maximum stress occurs at the cross section at a distance of 2/9 of the pin length from the pin head and at 0° of this section, which orientation is made when the pin is at 270° of the main shaft. Comparing four working modes, it was found that the working life of the shredder pin could be doubled by changing the sides of the pin and rotate it along its axes by 180°. Highlights: The maximum stress distribution law of the shredder pin along 3 sides was found out. The weakest point on the pin was found out by the finite element transient analysis. Changing two end sides of the pin at a specific time can lengthen its working life.